Roadway illuminating equipment with rainwater collection function - ZHAO DENGQIANG (2017)
The invention relates to roadway illuminating equipment with a rainwater collection function. The roadway illuminating equipment comprises a lamp post, LED illuminating equipment bodies, a rainwater collection groove, an electricity supply part, a rainwater channel, a filtering part, a recycled water storage tank and a water purification part. By integrating the rainwater collection and purification parts on a traditional LED street lamp, rainwater is collected and purified, and the electricity supply operation is conducted on the LED lamp; and by electrically connecting a medium and small generators of the electricity supply part with the LED illuminating equipment bodies, the street lamp can be switched on automatically in the rainy or rainstorm weather, and the roadway driving safety in the severe weather causing bad views and the like is improved. 本发明涉及种具有雨水收集功能的道路照明设备，包括灯柱、LED照明设备、雨水收集槽、供电部件、雨水通道、过滤部件、中水储存箱和水净化部件。通过在传统LED路灯上集成雨水收集和净化部件，不仅收集和净化了雨水，还给LED灯进行了供电操作，并且通过供电部件中小型发电机与LED照明设备的电连接，在下大雨或暴雨天气，可以自动开启路